#TITLE_ALTERNATIVE# - ICHWAN KURNIAWAN (NIM : 13205197); Pembimbing : Dr. Ir. Syarif Hidayat; Dr. Ir. Nanang Haryant, ADHI
The rapid growth of electric power system has resulted a large of study in reliability of the power system to transmit electric power to consumer. One of interested thing that many researcher focus is to detect and classify fault accurately. This paper proposed the application of artificial neural networks to fault detection and location in transmission lines using sets of data available from a selected network model and simulation. This methode has been chosen due to accuration of detection and locate the distance of fault, good response to recognize pattern and has ability to learn. Also the desain of device that can be implemented in real field. The fault that can be occur are single line to ground, double line to ground, phase to phase and three phase fault. The result show that artificial neural networks have ability to classify and determine the distance of fault accurately, the error rate is 0.004%.